Effectiveness of Five-Element Regulatory Therapy for post-COVID syndrome: a retrospective cohort study - Ding, Ning; Zhou, Yunqiao; Zhang, Haolin; Xin, Xiyan; Ye, Yang; Li, Dong (Frontiers in Medicine, 2025)
IntroductionPost-COVID syndrome is characterized by persistent, unexplained symptoms including chronic cough, palpitations, insomnia, and fatigue that develop following SARS-CoV-2 infection without identifiable causes. Current treatments show limited efficacy, requiring alternative options. This study aims to observe the effectiveness of Five-Element Regulation Therapy (FERT), a Traditional Chinese medicine (TCM) intervention, in managing post-COVID syndrome.MethodsA retrospective cohort study was conducted using clinical records of 127 post-COVID syndrome patients from the TCM outpatient department of Peking University Third Hospital. The participants were divided into two groups: 81 cases receiving FERT treatment were assigned to the exposure group, while 46 cases undergoing conventional TCM therapy served as the control group. The treatment duration was 2 weeks for both groups, followed by immediate follow-up. The outcomes included the clinical cure rate and clinical response rate at 2 weeks after the treatment initiation.ResultsThe FERT group demonstrated superior clinical outcomes, achieving a 61.7% cure rate and 88.9% response rate, significantly higher than the control group’s 21.7% (p < 0.001) and 67.4% (p < 0.01), respectively.ConclusionThis study provides preliminary evidence that FERT may be superior to conventional TCM therapy in managing post-COVID syndrome. Results should be interpreted with heightened caution due to the study’s inherent limitations.